Non‐targeted metabolomics for the identification of plasma metabolites associated with organic anion transporting polypeptide 1B1 function - Kreetta Hämäläinen; Päivi Hirvensalo; Mikko Neuvonen; Aleksi Tornio; Janne T. Backman; Marko Lehtonen; Mikko Niemi (Wiley, 2024)
Abstract Our aim was to evaluate biomarkers for organic anion transporting polypeptide 1B1 (OATP1B1) function using a hypothesis‐free metabolomics approach. We analyzed fasting plasma samples from 356 healthy volunteers using non‐targeted metabolite profiling by liquid chromatography high‐resolution mass spectrometry. Based on SLCO1B1 genotypes, we stratified the volunteers to poor, decreased, normal, increased, and highly increased OATP1B1 function groups. Linear regression analysis, and random forest (RF) and gradient boosted decision tree (GBDT) regressors were used to investigate associations of plasma metabolite features with OATP1B1 function. Of the 9152 molecular features found, 39 associated with OATP1B1 function either in the linear regression analysis (p < 10−5) or the RF or GBDT regressors (Gini impurity decrease > 0.01). Linear regression analysis showed the strongest associations with two features identified as glycodeoxycholate 3‐O‐glucuronide (GDCA‐3G; p = 1.2 × 10−20 for negative and p = 1.7 × 10−19 for positive electrospray ionization) and one identified as glycochenodeoxycholate 3‐O‐glucuronide (GCDCA‐3G; p = 2.7 × 10−16). In both the RF and GBDT models, the GCDCA‐3G feature showed the strongest association with OATP1B1 function, with Gini impurity decreases of 0.40 and 0.17. In RF, this was followed by one GDCA‐3G feature, an unidentified feature with a molecular weight of 809.3521, and the second GDCA‐3G feature. In GBDT, the second and third strongest associations were observed with the GDCA‐3G features. Of the other associated features, we identified with confidence two representing lysophosphatidylethanolamine 22:5. In addition, one feature was putatively identified as pregnanolone sulfate and one as pregnenolone sulfate. These results confirm GCDCA‐3G and GDCA‐3G as robust OATP1B1 biomarkers in human plasma.